2019
DOI: 10.1093/mnras/stz364
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of common envelope jets supernovae and the fast transient AT2018cow

Abstract: We propose a common-envelope jets supernova (CEJSN) scenario for the fast-rising blue optical transient AT2018cow. In a CEJSN a neutron star (NS) spirals-in inside the extended envelope of a massive giant star and enters the core. The NS accretes mass from the core through an accretion disc and launches jets. These jets explode the core and the envelope. In the specific polar CEJSN scenario that we propose here the jets clear the polar regions of the giant star before the NS enters the core. The jets that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
147
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 55 publications
(90 reference statements)
5
147
3
Order By: Relevance
“…The resulting transient is described as a "common envelope jets supernova" by Soker et al (2019). One of the key points that Chevalier (2012) and Soker et al (2019) mention is that the distribution of common envelope ejecta is crucial in shaping the observed light curve (see Kleiser et al 2018, for a similar discussion in the context of rapidly-fading supernovae). Here, we pursue this line of examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting transient is described as a "common envelope jets supernova" by Soker et al (2019). One of the key points that Chevalier (2012) and Soker et al (2019) mention is that the distribution of common envelope ejecta is crucial in shaping the observed light curve (see Kleiser et al 2018, for a similar discussion in the context of rapidly-fading supernovae). Here, we pursue this line of examination.…”
Section: Introductionmentioning
confidence: 99%
“…MERGER-DRIVEN EXPLOSIONS 2.1. Inspiral, Merger, and Central Engine Following its inspiral through the common envelope, a compact object can tidally disrupt and merge with the helium core of the massive star (Zhang & Fryer 2001;Chevalier 2012;Soker & Gilkis 2018;Soker et al 2019). The disrupted material forms an accretion disk surrounding the now-central compact object.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various authors have already suggested that there might be a jet in AT 2018cow (Kuin et al 2019;Margutti et al 2019;Perley et al 2019;Soker, Grichener & Gilkis 2019). Due to the similarities with GRB-SNe, an off-axis GRB event, with a relativistic jet not directed along the line of sight, is a possibility.…”
mentioning
confidence: 98%
“…Alternatively, Soker et al (2019) interpret AT 2018cow as the result of a binary star where a neutron star inspirals into its red giant companion, accreting rapidly when it reaches the dense core. Jets are produced, which clear the polar regions of the supergiant, which then form the observed high-velocity material.…”
mentioning
confidence: 99%
“…It has been shown that it could not have been powered by radioactive decay (Prentice et al 2018;Margutti et al 2019;Perley et al 2019). Several models have been proposed to explain the observed properties: a stellar collapse leading to the formation of a magnetar (Prentice et al 2018;Margutti et al 2019), a luminous blue variable exploding in a non-uniform circum-stellar medium (Rivera Sandoval et al 2018), a SN from a lowmass hydrogen-rich star, a failed SN from a blue supergiant (Margutti et al 2019), a tidal disruption event (TDE; Liu et al 2018;Kuin et al 2018;Perley et al 2019), a jet driven by an accreting neutron star colliding with a giant star (Soker et al 2019), or a merger of white dwarfs (Lyutikov & Toonen 2018). However, the constraints on the nature of this explosion set by the host galaxy properties have not been explored thoroughly.…”
Section: Introductionmentioning
confidence: 99%